Extreme Procalcitonin Elevation without Proven Bacterial Infection Related to Amphetamine Abuse - András Lovas; Zsuzsanna Ágoston; Klára Késmárky; Péter Hankovszky; Zsolt Molnár (Case Reports in Critical Care)
Systemic inflammatory response with rhabdomyolysis and consequent multiorgan failure is a known sequela of psychotropic drug abuse. However, in cases with uncertain past medical history the initial diagnosis can be challenging. Here we report the case of a 21-year-old male who was admitted to the intensive care unit with severe neurological impairment caused by amphetamine intoxication. First laboratory investigations revealed extremely high serum procalcitonin (PCT) levels reaching a maximum concentration of 1640 ng/mL on the second day of observation. Although PCT has high sensitivity and specificity in differentiating bacterial sepsis from nonbacterial inflammation, our case report shows for the first time that it can be extremely elevated following serious amphetamine intoxication without bacterial infection.